The Plasma Fraction of Stored Erythrocytes Augments Pancreatic Cancer Metastasis in Male Versus Female Mice - Moore, Peter K. (2010)
BACKGROUND: Males with pancreatic cancer have decreased survival compared with females. Interestingly, perioperative blood transfusions have been shown to reduce survival in patients with pancreatic adenocarcinoma. Recent evidence incriminates blood transfusions from female donors as a causative factor in acute lung injury. We therefore hypothesize thatmalemice with pancreatic cancer will have greater tumor progression than female mice in response to transfusion. METHODS: Mice previously inoculated with pancreatic cancer cells received an intravenous injection of acellular plasma collected from single donor erythrocytes from either male or female donors. Control mice received an equal volume of intravenous saline. Necropsy to determine metastasis was performed in female mice at 4 wk status post-transfusion. The male group necessitated sacrifice at 3 wk post-transfusion due to clinical deterioration. RESULTS: Male mice developed more metastatic events than female mice, and this was accentuated when receiving blood from female donors. Male mice experienced weight loss within 2 wk of tail vein injection, and three mice in the male transfused groups died secondary to malignancy. Female mice did not manifest substantial weight loss, and did not die in the study time period. CONCLUSION: Male mice, compared with female, had significantly more metastatic events following transfusion of plasma from stored erythrocytes in an immuno-competent murine model of pancreatic adenocarcinoma. Moreover, the adverse effect of transfusion was augmented with female donor blood. These data are consistent with clinical outcomes from centers of excellence in treating pancreatic cancer and warrant further investigation.